Restorasi Harapan: Peran Konseling dalam Meningkatkan Orientasi Masa Depan Anak di Lembaga Pembinaan Khusus Anak Kelas I Palembang - Nurhandini, Nadia; Sujarwo, Sawi (Yayasan Kawanad, 2025)
This study aims to examine the role of counseling in enhancing the future orientation of child detainees involved in child protection cases at LPKA Class I Palembang. Utilizing a descriptive qualitative approach, the research involved four subjects with diverse backgrounds. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. Interventions were conducted through individual counseling and group counseling (Focus Group Discussion) to strengthen motivation, cognitive representation, and behavior. The results showed an increase in intrinsic motivation, more realistic future planning, and active participation in development activities. Counseling proved to help the subjects recognize their potential, boost self-confidence, and establish clear life goals. These findings emphasize the importance of counseling as a continuous program to support the success of child development efforts at LPKA.